Barriers and levers in screening and care for alcohol use disorders among French general practitioners: results from a computer-assisted telephone interview-based survey. Issue 2 (3rd April 2019) - Costa, Marie; Yaya, Issifou; Mora, Marion; Marcellin, Fabienne; Villotitch, Antoine; Berenger, Cyril; Tanti, Marc; Cutarella, Christophe; Polomeni, Pierre; Maradan, Gwenaelle; Roux, Perrine; Rolland, Benjamin; et al.
ABSTRACT: Alcohol use disorders (AUD) is a major public health concern. General practitioners (GP) must play a key role in identifying this disorder and offering appropriate interventions. The authors conducted a survey among French GP in the Provence – Alpes – Côte-d'Azur (PACA) region to better understand their practices regarding AUD. Random sampling was used to enrol 101 GP in a 15-minute survey. A Computer-Assisted Telephone Interview exploring demographic and professional characteristics was conducted using a questionnaire. One third (31.7%) of the participants systematically addressed alcohol use with their patients whereas six (5.9%) never addressed it. Logistic regression analyses showed that after adjustment for the number of AUD patients followed up (odds ratio [OR] = 1.92; 95% confidence interval [CI] [1.19, 3.08]) and GP interest in addiction medicine (5.41 [2.17, 13.40]), GP who systematically screened patients for AUD were more likely to accept controlled drinking as a therapeutic goal (5.41 [2.17, 13.33]), and to perceive patient denial of AUD as a major barrier to care (1.39 [0.60, 3.22]). GP providing care for AUD were more likely to monitor tobacco cessation (9.08 [2.60, 31.64]) and to prescribe opioid maintenance treatment (7.35 [2.52, 21.41]). Alcohol screening is insufficient in general practice in France. Providing updated guidelines is essential to foster experience in this field among GP.